GREEN ECONOMY PERSPEKTIF EKONOMI SYARI’AH DALAM MENINGKATAKAN KESEJAHTERAAN MASYARAKAT - Mutmainah; Hamzah, Amir; Agrarini, Galuh Mustika (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2024)
The emergence of the green economy due to the issue of global warming is caused by the environmental crisis caused by a shift in pragmatic human lifestyles. This condition requires everything to be fast and easy with the use of packaged products which results in a lot of used product waste that is not environmentally friendly. Therefore, the concept of going green emerged, namely the concept of green economy as an environmentally friendly concept that is in accordance with Islamic economic principles to support environmental development (pro-environment) which has an influence on the development of an economic system that is able to improve the welfare of society.This research is research aimed at analyzing the green economy from an Islamic economic perspective to improve community welfare. This research is library research (library research), Data analysis techniques using the Milles and Huberman model include: (1) data reduction, (2) data display, and (3) conclusion drawing. Results research Based on the discussion it can be concluded that: concept green economyor green economy is low carbon economic activity, saves resources (resource efficient), and is socially inclusive/socially inclusive, where this concept is in accordance with Islamic economic principles, namely Islamic Eco-Ethics consisting of several principles basic Islamic ethics such as al-adl (justice), maslahah (public needs), urf (customs), istishlah (improvement), and i'tidal (harmony), so that the green economy is a form of economic improvement that is in harmony with nature in achieving the benefit and well-being.